An Assessment Of Serum Magnesium & It’s Association With Spirometry In Bronchial Asthma (Journal of Pharmaceutical Negative Results, 2022)
Asthma being a significant non communicable disease affecting 300 million people worldwide. It poses a major detrimental health and economic burden. Magnesium is the fourth most abundant cation in our body and the second most common intracellular cation. Magnesium is an important determinant of contraction and relaxation state of bronchial smooth muscle. Deficiency of magnesium can lead to lack of smooth relaxation and can worsen outcomes in asthmatics. The present study was done to evaluate the serum magnesium level & its impact on spirometry in asthmatics.